Prolonged exposure does not increase soil microbial community compositional response to warming along geothermal gradients - Radujkovic, Dajana; Verbruggen, Erik; Sigurdsson, Bjarni D.; Leblans, Niki; Janssens, Ivan; Vicca, Sara; Weedon, James (FEMS Microbiology Ecology, 2018)
Abstract: Global change is expected to affect soil microbial communities through their responsiveness to temperature. It has been proposed that prolonged exposure to elevated temperatures may lead to progressively larger effects on soil microbial community composition. However, due to the relatively short-term nature of most warming experiments, this idea has been challenging to evaluate. The present study took the advantage of natural geothermal gradients (from +1 degrees C to +19 degrees C above ambient) in two subarctic grasslands to test the hypothesis that long-term exposure (>50 years) intensifies the effect of warming on microbial community composition compared to short-term exposure (5-7 years). Community profiles from amplicon sequencing of bacterial and fungal rRNA genes did not support this hypothesis: significant changes relative to ambient were observed only starting from the warming intensity of +9 degrees C in the long termand +7 degrees C/+3 degrees C in the short term, for bacteria and fungi, respectively. Our results suggest that microbial communities in high-latitude grasslands will not undergo lasting shifts in community composition under the warming predicted for the coming 100 years (+2.2 degrees C to +8.3 degrees C).